Biogeographical status of dusky fruit bat, penthetor lucasi (chiroptera : Pteropodidae) inferred to morphological and genetic analyses in Malaysia - Mohd Ridwan, Abd Rahman (Universiti Malaysia Sarawak (UNIMAS), 2010)
The assessment of bats diversity from two limestone forests in protected areas of Sarawak, the Niah National Park (NP) and the Wind Cave Nature Reserve (NR) were conducted from November 2007 until April 2009. The assessments were aimed to update the current diversity of bats as well as to compile their composition with previous studies done at selected limestone areas in Sarawak. Eight to twelve mist nets and three harp traps were used, with accumulated effort of 572 trap-nights for both the Niah NP and the Wind Cave NR. A total of 1,520 individuals representing 36 species from 17 genera and 10 families were recorded. Penthetor lucas; Hipposideros eervinus and Cynopterus braehyotis were the three most abundant species captured in both sampling areas) Meanwhile, nine species of bats are new for both localities. Seven out of nine are the new additional records added for the Niah NP, namely, Hipposideros ater, H bieolor, H. cineraeeus, Coelops robinsoni, Rhinolophus trifoliatus, Murina rozendali and Kerivoliia hardwiekii. While H. ridleyi and Tylonyeteris robustula are new record for Wind Cave NR. Morphological analysis of70 adult individuals of P. lucasi was done using 15 characters and 18 craniodental characters. Three separate analyses were done onto these morphology data, namely, clustering analysis (CA), multiple regression and discriminant function analysis (DFA). CA analysis was done to construct a morphometric based phenogram and to assess grouping of of P. I/leasi populations. Multiple regression and discriminant function analysis were applied to test the effects of sex, location and interaction between individuals in this study, and to determine and identify characters which were useful in differentiating individuals among populations. CA showed that all specimens from the three different populations were mixed up and were not grouping accordingly to their populations. Through multiple regression analysis, most characters were significantly affected by sex (TB, D5PIL, OSL, PL, DL, C1BW and C1CIB); locality (E, TB, HF, D4PIL, D5PIL, lOW, MW and GBPL); and their interaction (E, TB, HF, D4PIL, D5PIL, GSL, lOW, MW, PL, PPL, GBPL, and CICIB). Thus, separate analyses were done for both sexes. The D4MCL and BL of male and HF and DL of female were suggested as the best predictors for the external and craniodental characters respectively in differentiating the P. lucasi of different localities. The findings for the morphological analysis have violated the early assumption of no morphological variation between the populations of P. lucasi. It is suggested that different ecological factor such as breeding, foraging behaviour and resource availability could have influenced the morphological variation of P. lucas; populations. The population genetics of the P. lucasi was inferred using 1,061 base pairs (bp) of the Cytochrome b mitochondrial gene. A total of 77 individuals of P. lucasi were classified a priori accordingly to their localities, namely, Miri, Kuching, Sri Aman and Kelantan populations. The findings showed that the P. lucasi populations were separated into two haplogroups, namely, Haplogroup 1 (containing Miri and Kuching populations) and Haplogroup 2 (the mixture of Miri, Kuching, Sri Aman and Kelantan populations). This separation was supported with high bootstrap values in all four methods of analysis (100% in neighbour joining; 100% in maximum parsimony; 94.9% in maximum likelihood and 100% in Bayesian). The occurrence of two haplogroup was address to unclear status of P. lucasi. High genetic divergence detected between the two haplogroups (3.88%) and separation between the haplogroups is predicted as the ancient events. The historical event includes the multiple colonisation and refugia during ice age period likely the main factors led to such separation. High divergence within the Miri (0.01 - 4.93%) and the Kuching (0.01 4.72%) populations was expected the occurrence of two putative species within P. lucasi. The presence of haplotypes from both populations in Haplogroup 1 and Haplogroup 2 is might be due to ability to perform high distance flight for foraging. High gene flow between these populations (Nm= -16.64) suggest the continuous distribution of P. lucasi judging from the distance of both localities. Absences of deep structure from the haplotypes tree further prove that P. lucasi has wide dispersal ability. The discrepancies of morphological and genetic data were suggested due to different evolutionary rates and the morphological features could have evolved faster than those of the mtDNA gene. However, further studies involving additional and adequate geographic representatives from the Borneo (especially from Gomantong, Madai and Mulu Caves) and Peninsular Malaysia could properly address the incongruence results of both analyses. This would also enable further verification of the hypothesis generated in this study.